A Comparative Study on the Effectiveness of Electroconvulsive Therapy and Ketamine in Persons Suffering from Treatment-resistant Depressive Disorder - Vikhram Ramasubramanian; S. Mathumathi; Gautami Thirumalaisamy; Sugaparaneetharan Ayyanar; Gopi Rajendhiran; M. Kannan (Indian Journal of Psychiatric Nursing)
Background: Depression is a common illness that affects about 3.8% of the population worldwide. Patients with major depression respond to antidepressant treatment, but 10%–20% of them do not improve or show a partial response. It is coupled with functional impairment, poor quality of life, suicide ideation and attempts, self-injurious behavior, and a high relapse rate. Treatment-resistant depression (TRD) is a challenge to clinicians because of its increased loss of functionality and the increased rate of suicide among people diagnosed with the illness. Studies are evolving to combine various treatment options to reduce morbidity and mortality in people suffering from the illness. This study aims at comparing the efficacy of electroconvulsive therapy (ECT) and ketamine transfusion in treating TRD. It hopes to prove that ketamine provides rapid relief for people suffering from TRD. Materials and Methods: A prospective, parallel randomized controlled, open label, noninferiority/superiority trial to compare the efficacy of ECT and ketamine was done. Ninety-six persons suffering from TRD were selected for the study through proportionate stratified random sampling and 46 persons received 6 ECT treatment and 50 persons received six doses of ketamine. Treatment response was measured using Hamilton depression ratings scale (HAM-D) using baseline, mid assessment, and postassessment scores. The scores were used to determine the effectiveness of ECT and ketamine in the treatment of TRD. Results: Ketamine was proven to have the same antidepressant effect in participants as that of ECT. Ketamine was observed to have rapid reduction in depressive symptoms when compared to ECT. Conclusion: This study highlights that ketamine can be considered as an effective alternative to ECT in those with TRD.